Alleluia non meremur in perenne psallere. Notas sobre la evolución del oficio aleluyático de septuagésima en Cataluña y el Languedoc - Rubio Sadia, Juan Pablo (Miscel·lània litúrgica catalana, 2012)
In the context of the introduction of the Roman Liturgy in the Carolingian churges, there had been stablished, normally on the «Dominica in Septuagesima», an office in honour of the Alleluia, a canticle forbidden from that day up to the Easer Vigil. This singular office, with precedents in the Spanish Liturgy, acquired particular regional expressions in the 9th and 10th centuries, and started to be supressed in the second half of 11th century, as a consequence of the liturgical reformation imposed from Rome. In this article, with the liturgical sources as a ground, it is intended to follow this process of liturgical reformation of the Septuagesima in the churches of Catalonia and the Languedoc in the 10th and 11th centuries. The main aim is to know how this feast was celebrated and which criteria were followed by local liturgists to adapt the old formularies to the new papal regulations.